Towards a direct collapse load method of design for concrete frames subjected to severe ground motions. - Griffith, M.C (Earthquake engineering & structural dynamics.)
Most current methods of design for concrete structures under earthquake loads rely on highly idealized 'equivalent' static representations of the seismic loads and linear elastic methods of structural analysis. With the continuing development of non-linear methods of dynamic analysis for the overload behaviour and collapse of complete concrete structures, a more direct and more accurate design procedure becomes possible which considers conditions at system collapse. This paper describes an evaluation procedure that uses non linear dynamic collapse load analysis together with global safety coefficients. A back calibration procedure for evaluating the global safety coefficients is also described. The aim of this paper is to open up discussion of alternative methods of design with improved accuracy which are necessary to move towards a direct collapse load method of design.